2014
DOI: 10.1159/000362694
|View full text |Cite
|
Sign up to set email alerts
|

Food Intake and Overweight in School-Aged Children in Germany: Results of the GINIplus and LISAplus Studies

Abstract: Objective: To investigate the cross-sectional association between food intake and overweight in children. Methods: Height and weight were measured in 2,565 school-aged children. Intakes of 11 food groups were categorized (low, medium and high) using specific tertile cutoffs. Multivariate energy partition models were applied. Adjustment included energy intake from other food groups, city, family income, parental education and ‘screen' time. Possible underreporters were identified and used in sensitivity analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
(69 reference statements)
3
11
0
1
Order By: Relevance
“…Our study population consisted of children assessed over a five-year follow-up period during adolescence, from ages 10 to 15 years. We have previously reported cross-sectional associations between higher total meat intakes and increased BMI in 10-year old children from the GINIplus and LISAplus birth cohort studies [21]. Additionally, Bradlee et al [25] reported that adolescent boys (aged 12–16) with smaller waist circumferences tended to eat less meat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study population consisted of children assessed over a five-year follow-up period during adolescence, from ages 10 to 15 years. We have previously reported cross-sectional associations between higher total meat intakes and increased BMI in 10-year old children from the GINIplus and LISAplus birth cohort studies [21]. Additionally, Bradlee et al [25] reported that adolescent boys (aged 12–16) with smaller waist circumferences tended to eat less meat.…”
Section: Discussionmentioning
confidence: 99%
“…First, minimally adjusted models (MIN) were fit, adjusting for study, recruitment region, parental education level, pubertal onset, age at BIA measurement and sedentary behaviour. As significant associations between meat intake and BMI at age 10 years have been previously reported [21], main models (MAIN) were fit separately, further adjusting for weight category at age 10 years. We performed additional analyses where we further adjusted the main model for EAA, SFA, MUFA or PUFA, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, the literature has reported conflicting results. Some studies have shown a direct relationship between obesity and the consumption of breads and cereals (25,26), and some have reported an inverse association between obesity and fruit and vegetable intake (27,28). A study showed an inverse association between obesity and the consumption of red meat (27), while others (25,26) have reported a positive association between these two.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown a direct relationship between obesity and the consumption of breads and cereals (25,26), and some have reported an inverse association between obesity and fruit and vegetable intake (27,28). A study showed an inverse association between obesity and the consumption of red meat (27), while others (25,26) have reported a positive association between these two. On the other hand, there are some reports indicating that obesity is positively associated with dairy products intake (26,28), while others have shown an inverse relationship (27).…”
Section: Discussionmentioning
confidence: 99%
“…In general, FFQs poorly identify the important contribution from other product sources such as dairy, pastries, desserts, cereals and spreads [15]. Moreover, the cocoa percentage in chocolate bars is not always inquired about, though the presence of polyphenols is totally different among white, milk or the different types of dark chocolates [16,17]. These facts support the need for an assessment of cocoa product consumption in order to evaluate the actual cocoa intake, especially in the young population, who frequently consume chocolate without being aware of its benefits.…”
Section: Introductionmentioning
confidence: 99%